High Correlation between Oxidation Loci on Graphene Oxide1. (13th July 2014) - Yang, Jinrong; Shi, Guosheng; Tu, Yusong; Fang, Haiping
Abstract Recent experiments have shown the coexistence of both large unoxidized and oxidized regions on graphene oxide (GO), but the underlying mechanism for the formation of the GO atomic structure remains unknown. Now, using density functional calculations, 52 oxidation pathways for local pyrene structures on GO were identified, and a kinetic profile for graphene oxidation with a high correlation between oxidation loci was proposed, which is different from the conventional view, which entails a random distribution of oxidation loci. The high correlation is an essential nature of graphene oxidation processes and can be attributed to three crucial effects: 1) breaking of delocalized π bonds, 2) steric hindrance, and 3) hydrogen‐bond formation. This high correlation leads to the coexistence of both large unoxidized and oxidized regions on GO. Interestingly, even in oxidized regions on GO, some small areas of sp2‐hybridized domains, similar to "islands", can persist because of steric effects.